PERANAN DPRD KABUPATEN TEBO DALAM MELAKSANAKAN FUNGSI PENGAWASAN TERHADAP PERATURAN DAERAH TENTANG RETRIBUSI PELAYANAN PASAR - Pebriani, Rizki; Syamsir, Syamsir; Bustanuddin, Bustanuddin (Universitas Jambi, Fakultas Hukum, 2023)
AbstrakThis research is based on the Regional People's Legislative Council (DPRD) which is a regional people's representative institution that is located as an element of Regional Government administration. DPRD is responsible for carrying out one of the management functions of the regional government, namely controlling and supervising. However, in practice this very vital function is not carried out perfectly and satisfactorily. Based on the real conditions that occur in the field, the realization of local tax and regional retribution revenues has not yet reached the target according to the time set each year. This turned out to be inseparable from the problem of achieving regional tax and regional retribution targets in order to increase local revenue, the problem that occurs in the field is that the target of regional tax and regional retribution revenues has not been achieved in all sectors. The problem in this study is how the function of the Regional People's Representative Council (DPRD) of Tebo Regency in carrying out the supervisory function of Regional Regulation No. 15 of 2010 concerning market service fees and what factors support and hinder efforts to carry out the supervisory function of market service fees in Tebo district. The purpose of this study was to determine the function of the Regional People's Representative Council (DPRD) of Tebo Regency in carrying out the supervisory function of Regional Regulation No. 15 of 2010 concerning Market Service Charges and to find out the factors that support and hinder the implementation of the DPRD's supervisory function on the implementation of Regional Regulation No. 15 of 2010 concerning market service fees. This study used empirical juridical research methods with the research location at the Tebo Regency Industry and Trade Service with samples interviewing the head of the Tebo Regency Industry and Trade Office Market, 2 reception staff and the reception treasurer. The results of this study are that the Regional People's Representative Council (DPRD) is part of the regional government, because in a unitary state there is no regional legislature, therefore DPRD is included in the administration of regional government. In running the government, the authority of the DPRD is not like the authority of the Regional Head who has so much authority, so that the domination of authority in running regional government lies with the Regional Head, this shows that actually the role of the DPRD is only as a complement in running governance in the region, even though the DPRD has a supervisory function. but in terms of implementation, has it been carried out effectively, bearing in mind that the DPRD is also part of the regional government, of course it will be difficult to carry out this task, because the DPRD cannot act independently like the DPR of the Republic of Indonesia. The factors that influence the implementation of market retribution collection policies in the Tebo Regency market include: communication, resources and facilities andinfrastructure. Keywords: The Role and Function of DPRD Oversight, Market Service Retribution Abstrak Penelitian ini didasari oleh Dewan Perwakilan Rakyat Daerah (DPRD) adalah lembaga perwakilan rakyat Daerah yang berkedudukan sebagai unsur penyelenggaraan Pemerintahan Daerah. DPRD bertanggung jawab melaksanakan salah satu fungsi manajemen pemerintah daerah yaitu pengendalian dan pengawasan (controlling and supervisison). Namun dalam prakteknya fungsi yang sangat vital ini tidak dilaksanakan secara sempurna dan memuaskan. Berdasarkan kondisi nyata yang terjadi dilapangan, realisasi penerimaan pajak daerah dan retribusi daerah belumlah mencapai target sesuai waktu sebagaimana yang telah ditetapkan setiap tahunnya. Hal tersebut ternyata tidak lepas dari adanya masalah terhadap pencapaian target pajak daerah dan retribusi daerah guna meningkatkan penerimaan pendapatan asli daerah, masalah yang terjadi dilapangan yaitu masih belum tercapainya target penerimaan pajak daerah dan retribusi daerah disegala sektor. Permasalahan dalam penelitian ini adalah bagaimana fungsi Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Tebo dalam melaksanakan fungsi pengawasan terhadap Peraturan Daerah No. 15 tahun 2010 tentang Retribusi Pelayanan Pasar dan faktor apa saja yang mendukung dan menghambat dalam mengupayakan fungsi pengawasan dari hasil pungutan Retribusi Pelayanan pasar di Kabupaten Tebo. Tujuan penelitian ini adalah untuk mengetahui fungsi Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Tebo dalam melaksanakan fungsi pengawasan terhadap Peraturan Daerah No. 15 tahun 2010 tentang Retribusi Pelayanan Pasar dan untuk mengetahui faktor-faktor yang mendukung dan menghambat implementasi fungsi pengawasan DPRD terhadap pelaksanaan Peraturan Daerah No.15 tahun 2010 tentang retribusi pelayanan pasar. Penelitian ini menggunakan metode penelitian yuridis empiris dengan lokasi penelitian di Dinas Perindustrian dan Perdagangan Kabupaten Tebo dengan sampel mewawancarai kabid Pasar Dinas Perindustrian dan Perdagangan Kabupaten Tebo, 2 orang pegawai bagian penerimaan dan bendahara penerimaan. Hasil dari penelitian ini adalah Dewan Perwakilan Rakyat Daerah (DPRD) merupakan bagian dari pemerintah daerah, karena di dalam negara kesatuan tidak ada legislatif daerah, oleh karenaitu DPRD dimasukkan ke dalam penyelenggaraan pemerintah daerah. Dalam menjalankan pemerintahan, kewenangan DPRD tidak sepertikewenangan Kepala Daerah yang memiliki kewenangan begitu besar, sehingga dominasi kewenangan dalam menjalankan pemerintahan daerah berada pada Kepala Daerah, hal ini menunjukkan bahwa sebenarnya peranan DPRD hanyalah sebagai pelengkap saja dalam menjalankan pemerintahan di daerah, walaupun DPRD mempunyai fungsi pengawasan tetapi pada implementasinya apakah sudah dijalankan secara efektif, mengingat bahwa DPRD juga merupakan bagian dari pemerintah daerah, tentu saja akan sulit menjalankan tugas ini, karena DPRD tidak bisa berlaku independen seperti DPR Republik Indonesia. Adapun faktor-faktor yang berpengaruh dalam implementasi kebijakan pemungutan retribusi pasar di pasar Kabupaten Tebo, antara lain: komunikasi, sumber daya dan sarana danprasarana.Kata kunci : Peranan dan Fungsi Pengawasan DPRD, Retribusi Pelayanan Pasar